PENGENALAN INTERNET OF THINGS (IOT) SEBAGAI UPAYA UNTUK MENUNGKATKAN WAWASAN SISWA MTS MATHLAUL ANWAR DALAM DUNIA INDUSTRI 4.0 - Roeslan Djutalov; Tri Prasetyo; Pandu Wiliantoro (Abdi Jurnal Publikasi, 2023)
Along with the development of a technology that can assist in the field of teaching, one that can be utilized by schools is the Internet of Things (IOT). Technology that can be utilized in the Internet of Things (IOT) sector, especially for students, is technology using the C++ application language. the target of Community Service (PkM) is students at the MTS Mathlaul Anwar Pamulang school, South Tangerang City. The main focus of this Community Service (PkM) is to introduce the Internet of Things and an internet-based simulation site at the MTS Mathlaul Anwar Pamulang school. The purpose of this activity is to introduce students so they can find out what are the supporting components for making the internet of things,